Efforts to Prevent Engineers' Work Accidents at KM Intan Daya: Case Study: The Occurrence of an Accident in the Main Engine Repair Process when Lifting the Piston of the Main Engine on the Ship - Mursidi, Mursidi; Mahrus, Farras Ferdinan; Mata, George Jonhanes Bara (Universitas Hang Tuah, 2024)
Lack of attention from the company and ship's crew to work safety. It can be seen from the work safety equipment supplied by the company for crew members who only use helmets and gloves, and also some crew members who carry out overhaul work on the main engine do not wear safety shoes. In dealing with and preventing work accidents on ships, especially in the engine room, workers (crew) should be equipped with Personal Protective Equipment (PPE). Lack of familiarization as new crew members, lack of skills, experience and knowledge of crew members in the engine section regarding work safety. It is interesting to note that experienced crew members are less likely to experience an accident than crew members who are new to carrying out their work. This is because experience and length of time working in a particular skill plays a role in avoiding accidents. Based on experience, many incidents ranging from near misses to serious accidents occur on ships. Based on this, it is also something that is very important for planning safety programs, so that possibilities and losses resulting from these events can be prevented. Case Study, the fall of cylinder piston no. 3 main engines. KM. INTAN DAYA almost fell on one of the oilmen during an overhaul which caused damage to the material or piston. This is due to the lack of introduction of new crew members to awareness and the dangers of other work accidents.